Efektywność w ujęciu mikro- i makroekonomicznym w myśli ekonomicznej — przegląd teoretyczny - Borkowski, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The main purpose of this article is the presentation of the evolution of efficiency in economic theory. The article bears the features of a rational reconstruction of the economic thought. The study uses the method of critically analyzing literature on the subject as a tool to achieve the adopted objective. The article is theoretical in nature, trying to organize the theory of economics into efficiency categories. In order to improve transparency, the analysis has been split into micro- and macroeconomic approaches to efficiency. The article presents a chronological, synthetic order of economic thought achievements in terms of efficiency.Literature analysis indicates that, over the years, the way of understanding efficiency, in both micro- and macroeconomic terms, has significantly developed and changed. It seems that, despite so many analyses, there is still, and probably will always be, a lack of one versatile and universally accepted definition of efficiency. The lack of a single, well-established definition of efficiency, both on a micro- and macroeconomic scale, results in the diversity of approaches to measuring this category.
Keywords: efficiency; efficiency of the economy; economic thought